Judgment aggregation functions and ultraproducts - Frederik Herzberg (Bielefeld University, Institute of Mathematical Economics (IMW), 2008)
The relationship between propositional model theory and social decision making via premise-based procedures is explored. A one-to-one correspondence between ultrafilters on the population set and weakly universal, unanimity-respecting, systematic judgment aggregation functions is established. The proof constructs an ultraproduct of profiles, viewed as propositional structures, with respect to the ultrafilter of decisive coalitions. This representation theorem can be used to prove other properties of such judgment aggregation functions, in particular sovereignty and monotonicity, as well as an impossibility theorem for judgment aggregation in finite populations. As a corollary, Lauwers and Van Liedekerke's (1995) representation theorem for preference aggregation functions is derived.
urn:nbn:de:hbz:361-14216
Keywords: D71; 330; Judgment aggregation function; Ultraproduct; Ultrafilter; Präferenztheorie; Aggregation; Soziale Wohlfahrtsfunktion; Theorie